Teaching English Through Cultural Content: Enhancing Language Learning and Intercultural Competence (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
Teaching English as a foreign language has evolved beyond traditional grammar-based instruction to include communicative and cultural approaches. One of the most effective modern strategies is teaching English through cultural content. This study explores the role of cultural integration in English language teaching (ELT) and its impact on learners’ language development and intercultural competence. Using a qualitative descriptive approach, the study examines classroom practices, teaching materials, and learner responses. The results indicate that cultural content increases learner motivation, improves vocabulary acquisition, enhances communicative competence, and develops intercultural awareness. The study concludes that integrating culture into English lessons significantly contributes to effective language learning in modern education systems.